2015
DOI: 10.1111/sms.12450
|View full text |Cite
|
Sign up to set email alerts
|

High physical activity in young children suggests positive effects by altering autoantigen‐induced immune activity

Abstract: Physical activity in children is associated with several positive health outcomes such as decreased cardiovascular risk factors, improved lung function, enhanced motor skill development, healthier body composition, and also improved defense against inflammatory diseases. We examined how high physical activity vs a sedentary lifestyle in young children influences the immune response with focus on autoimmunity. Peripheral blood mononuclear cells, collected from 55 5-year-old children with either high physical ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
0
8
1
1
Order By: Relevance
“…Some studies have suggested that a sedentary lifestyle may lead to a deteriorated immune response. 2 We, however, did not observe any association between sedentary behavior and WBC count or any subfraction. 9 Therefore, our findings corroborate the results of a previous meta-analysis which indicate that there is limited available evidence demonstrating that the overall volume or patterns of sedentary behavior are associated with health and development in children and young people.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…Some studies have suggested that a sedentary lifestyle may lead to a deteriorated immune response. 2 We, however, did not observe any association between sedentary behavior and WBC count or any subfraction. 9 Therefore, our findings corroborate the results of a previous meta-analysis which indicate that there is limited available evidence demonstrating that the overall volume or patterns of sedentary behavior are associated with health and development in children and young people.…”
Section: Discussioncontrasting
confidence: 65%
“…It has been previously suggested that high PA in young children suppresses the immune activity and induces anti-inflammatory effects. 2 The current study found that meeting the international PA recommendations was weakly associated with lower total WBC count and with higher odds of depicting a normal range in this parameter in both, boys and girls. Similarly, boys who were active had lower neutrophil concentration in comparison with more inactive counterparts.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Carlsson et al stimulated peripheral blood mononuclear cells from children with high versus average physical activity. The authors found that high physical activity was associated with lower immune reactivity toward autoantigens GAD65, HSP60, and IA-2 and also with lower spontaneous pro-inflammatory immune activity [ 32 ▪ ].…”
Section: Classical Risk Factors Of Cardiovascular Diseases Are More Cmentioning
confidence: 99%
“…Carlsson et al demonstrierten bei fünfjährigen Kindern, dass sich die Reagibilität von mononukleären Zellen (Sekretion von IL-6, IL-13, IFN-γ, TNF-α und CCL-2) gegenüber Autoantigenen (GAD65, Insulin, HSP60 und IA-2) in Abhängigkeit vom körperlichen Aktivitätsniveau unterscheidet (29). Hierbei zeigte sich, dass die Zellen von Kindern mit viel körperlicher Aktivität signifikant weniger spontane proinflammatorische Aktivität und zusätzliche eine verminderte Aktivität gegenüber Autoantigenen zeigten.…”
Section: Sport Und Autoimmunitätunclassified